Antibacterial Activity of Residual Seeds and Pods of Annatto (Bixa orellana L.) After Pigment Extraction - Aluko, Ebenezer Olanrewaju; Adetuyi, Abayomi Olagundoye; Omotoso, Ezekiel (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
Recent studies have demonstrated that annatto seeds contain a variety of metabolites with antimicrobial properties. Correspondingly, this research investigated the antimicrobial activity of extracts from annatto (Bixa orellana) seeds, pods, and their combination. As part of a strategy to convert waste into valuable resources, this study evaluated the antimicrobial potential of residual extracts derived from annatto seeds and pods. Ethanol extracts of pigment-extracted annatto seeds, pods, and their mixture were tested against Escherichia coli, Streptococcus faecalis, Staphylococcus aureus, and Bacillus subtilis using the agar well diffusion method. Streptomycin and ampicillin (10 mg/mL each) served as positive controls, while an ethanol-water mixture (1:1) served as the negative control. All three extracts exhibited varying activity levels against the tested bacteria. They were most effective against B. subtilis, with inhibition zones measuring 11.5 ± 0.5 mm, 14.5 ± 0.5 mm, and 23.5 ± 0.5 mm for the seed, pod, and seed-pod extract mixture, respectively. In contrast, they exhibited the least activity against E. coli, with inhibition zones of 6.0 ± 2.0 mm, 5.5 ± 1.5 mm, and 11.0 ± 0.0 mm for the respective extracts. Post-hoc Tukey's test revealed that the combination of seed and pod extracts demonstrated significantly higher antimicrobial activity than the individual extracts (p < 0.001) against all tested organisms. Notably, the combined extract demonstrated comparable activity to ampicillin against B. subtilis (p > 0.05) and significantly higher activity than streptomycin (p < 0.001) against all tested strains except S. aureus. The pronounced antimicrobial efficacy of the seed and pod extracts, especially when combined, contributes to the growing body of evidence supporting the potential of Bixa orellana as a natural antimicrobial agent effective against both Gram-positive and Gram-negative bacteria.